What Determines the Number of Bank Relationships? Cross-Country Evidence - Ongena, Steven; Smith, David C. (Journal of Financial Intermediation, 2000)
We investigate the determinants of multiple-bank relationships using a new data set comprising 1079 firms across 20 European countries. We document large cross-country variation in the average number of bank relationships per firm, uncovering a richness in European financial systems that extends beyond the standard description of being “bank-dominated”. After controlling for a variety of firm-specific characteristics, we find that firms maintain more bank relationships, on average, in countries with inefficient judicial systems and poor enforcement of creditor rights. Firms also maintain more relationships in countries with unconcentrated but stable banking systems and active public bond markets. Journal of Economic Literature Classification Numbers: G21, C41.